Histopathological Changes that Occur on the Testicular and Penile Tissues Depending on the Treatment of Human Chorionic Gonadotropin: Rat Model - Pirincci, N.; Yildirim, S.; Tas, A.; Ozan, T.; Gecit, I; Ozveren, H. (Univ West Indies Faculty Medical Sciences, 2021)
Objective: To examine the histopathological effects of human chorionic gonadotropin (hCG) treatment on the penile and the testicular tissue in rat model. Methods: The rats of the hCG group (n = 8) were given daily subcutaneous injections of 50 IU of hCG for 15 days (Pregnyl, Organon). Rats of the control group (n = 8) received subcutaneous isotonic saline. All rats were sacrificed at the 1st month after hCG administration. After the received tissue samples were examined, germinal epithelial cell thickness, seminiferous tubule diameter; internal diameter of the tubules, the number of germ cell layers in the testicular tissue, and the diameters of penis, cavernous sinus lumen diameters and collagen tissue amount in the cavernous sinus surrounding were assessed in the sections prepared from the penis. Results: It was detected that there was a decrease in the testis weight, atrophy in the tubules, reduction in spermatogenesis, decrease in the mature spermatocytes, lower mean thickness and the number of cell layers of the germinal membrane in testicular tissue in the hCG group. It was found that the amount of collagen in the penile tissue was significantly higher in the hCG group and the diameters of cavernosal sinus lumens, and diameter of the penis were significantly lower in the hCG group. Conclusion: Human chorionic gonadotropin led to the deterioration in testicular histology and the histological changes in the penile tissue. The degradation in the testicular tissue and these changes formed in the penile tissue may affect the erectile tissue function.
Keywords: Histopathology; human chorionic gonadotropin; penile; rat; testicular